Magnetic resonance phase contrast velocity mapping for flow quantification in irregular heart rhythms using radial k-space ultrashort echo time imaging - Hell, Michaela; Francis, Jane M.; d'Arcy, Joanna; Robson, Matthew D.; Neubauer, Stefan; Achenbach, Stephan; Myerson, Saul G. (International Journal of Cardiology, 2020)
Background: Phase contrast velocity mapping sequences utilising ultrashort echo time (UTE) radial k-space sequences have been used to reduce intravoxel dephasing at high velocities. We evaluated the accuracy of the UTE flow sequence for mitral regurgitation (MR) quantification, including patients with atrial fibrillation. Methods: Forty patients underwent cardiac MRI for indirect MR quantification by assessment of aortic flow using a UTE phase contrast sequence (TE 0.65 ms) combined with left ventricular stroke volume. Retrospective ECG-gating was used in sinus rhythm (30 patients), prospective ECG-triggering in atrial fibrillation (10). MR was also quantified by a standard phase contrast sequence (TE 2.85 ms, standard flow method) and by comparing stroke volumes (volumetric method). Results: UTE flow-derived MR measurement showed modest agreement in sinus rhythm (95% limits of agreement: ±38.2 ml; ±29.8%) and atrial fibrillation (±33.7 ml; ±30.3%) compared to standard flow assessment. There was little systematic bias in sinus rhythm (mean offset −4.4 ml /−3.5% compared to standard flow assessment), but a slight bias towards greater regurgitation in atrial fibrillation (+15.2 ml /+14.0%). There were wider limits of agreement between the UTE flow method and volumetric method than between the regular flow method and the volumetric method in sinus rhythm (±48.4 ml; ±36.4%; mean offset: −12.2 ml /−9.0%) and similar limits of agreement in atrial fibrillation (±29.6 ml; 25.8%; +12.0 ml /+10.3%). Conclusions: UTE flow imaging is inferior to conventional flow techniques for MR assessment in patients with sinus rhythm as well as atrial fibrillation. However, the number of atrial fibrillation patients in this initial study is small.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Atrial fibrillation; ultrashort echo time imaging; Cardiac magnetic resonance; Flow imaging; Mitral regurgitation